NASAL ADMINISTRATION OF SILVER NANOPARTICLES AND SILVER IONS REDUCED COGNITIVE PERFORMANCE IN ADULT RATS - Farimaneh, Javad; Tabandeh, Mohammad Reza; Tabatabaei, Seyed Reza Fatemi (Universal Journal of Pharmaceutical Research, 2023)
Background: Silver nanoparticles (AgNPs) have shown adverse effects and a toxic impact on human cell bodies. Passing the blood-brain barrier and increasing oxidative stress can change different parts of the brain such as the hippocampus. Therefore, the purpose of this investigation was to explore the possible neurotoxicity of AgNPs in adult rats. Method: Neurotoxicity was created in rats by treating them with 15 mg/kg NP3 and silver ions (AgAc) intra-nasally every two days for 20 days. The animals were divided into five groups: control, vehicle, NP3, NP15, and AgAc. Behavioral assessments such as Morris water maze and elevated plus maze, and assessment of biomarkers such as malondialdehyde assay were used to evaluate cognitive impairment and molecular changes induced by silver. Result: The results revealed that NP15 and AgAc significantly impaired spatial memory. Moreover, NP3, NP15, and AgAc increased anxiety in animals. Additionally, MDA was significantly increased by NP3 and NP15. Conclusion: The findings showed that AgNPs and AgAc, particularly NP15, result in neurotoxicity and behavioral impairments. Peer Review History: Received: 3 February 2023; Revised: 10 March; Accepted: 25 April 2023, Available online: 15 May 2023 Academic Editor: Dr. Nuray Arı , Ankara University, Turkiye, ari@ankara.edu.tr Reviewers: Dr. Sally A. El-Zahaby, Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, King Salman International University, Egypt, sally.elzahaby@yahoo.com Dr. Robert Tungadi, State University of Gorontalo, Indonesia, rtungadi@yahoo.com